Can type 1 diabetes be an unexpected complication of obesity? - Oboza, Paulina; Ogarek, Natalia; Olszanecka-Glinianowicz, Magdalena; Kocelak, Piotr (Frontiers in Endocrinology, 2023)
Type 1 diabetes (T1D) is one of the most common chronic autoimmune diseases, characterized by absolute insulin deficiency caused via inflammatory destruction of the pancreatic β-cell. Genetic, epigenetic, and environmental factors play a role in the development of diseases. Almost ⅕ of cases involve people under the age of 20. In recent years, the incidence of both T1D and obesity has been increasing, especially among children, adolescents, and young people. In addition, according to the latest study, the prevalence of overweight or obesity in people with T1D has increased significantly. The risk factors of weight gain included using exogenous insulin, intensifying insulin therapy, fear of hypoglycemia and related decrease in physical activity, and psychological factors, such as emotional eating and binge eating. It has also been suggested that T1D may be a complication of obesity. The relationship between body size in childhood, increase in body mass index values in late adolescence and the development of T1D in young adulthood is considered. Moreover, the coexistence of T1D and T2D is increasingly observed, this situation is called double or hybrid diabetes. This is associated with an increased risk of the earlier development of dyslipidemia, cardiovascular diseases, cancer, and consequently a shortening of life. Thus, the purpose of this review was to summarize the relationships between overweight or obesity and T1D.